An Investigation on the Mix Design of Double Layer Porous Asphalts - Babak Golchin; Noor Halizah Abdullah; Meor Othman Hamzah; Jan Valentin (Journal of Rehabilitation in Civil Engineering)
Porous asphalt (PA) are used to drain water from the surface of the asphalt pavements. It reduces aquaplaning and subsequently decreases splash and spray. Clogging reduces the permeability of PA over the years. The double layer PA are used to mitigate this problem. Different aggregate gradations and binder types can alter the performance of double layer PA. The objective of this research is to evaluate the effects of these parameters on the performance of double layer PA. For this purpose, different samples were fabricated using various aggregate gradations based on Malaysian asphalt mixture standards. Indirect tensile strength, permeability and air voids of the samples were determined. The proposed aggregate gradation for top and bottom layers were mixed with two different asphalt binders. Cantabro and binder drainage tests were later carried out on these samples. The results were then compared with the corresponding results from the Dutch double layer PA gradations. Laboratory test results showed that aggregate gradation significantly affect the indirect tensile strength, permeability and air voids of both top and bottom layer of PA. The design binder content for the bottom layer is also lower than that for the top layer. However, the binder type did not significantly change the design binder content.